Pengaruh Kepemimpinan, Komunikasi dan Motivasi Terhadap Kinerja KaryawanPada Kantor Kementerian Agama Kabupaten Karanganyar - Dedi Irawan, Agus; , M. Farid Wajdi, Ph.D; , Soepatini, Ph.D (2016)
The purpose of this study is ( 1 ) to analyze the influence of leadership , communication , and motivation on employee performance in the Office of Religious Affairs of Karanganyar , ( 2 ) to analyze the dominant factors include leadership , communication , and motivation that affect the performance of employees in the Office of Religious Affairs Karanganyar . The sample in this pebelitian are 69 employees at the Ministry of Religious Karanganyar . Penggambilan questionnaire and analyzed the data using regression premises . The results showed that motivation variables significantly influence performance variables . This is evidenced by the value thitug > t table ( 3.337 > 1.669 ) and significance < 0.05 ( 0.001 < 0.05 ) , which means that Ho is rejected, there is a motivation variables were significant and positive effect on employee performance variables at the District Office of Religious Affairs Karangayar .